Coexistence Plant Model for an Automated Coexistence Management. Issue 1 (July 2017) - Schulze, Darina; Rauchhaupt, Lutz; Kraetzig, Marko; Jumar, Ulrich
Abstract: For data transmission of industrial applications parallel operations of various wireless communication systems are required in an industrial application environment. For guaranteeing that every application communication requirement of each wireless communication system is fulfilled, those systems have to be coexistent between each other. The process ensuring coexistence is called coexistence management process. In current approaches this holistic management is not considered yet. We want to develop an automated coexistence management with control engineering considerations. In this contribution we propose a basic model approach for a coexistence plant. For describing the structure and the time behaviour of a coexistence plant, Petri-net graphs are used. Therefore we split the state space into two description types. The first one describes the transfer of messages and the second one describes the time behaviour of state transition in the coexistence plant. Finally, the derived model on measurements in a 2:4 GHz frequency spectrum within a WiFi test environment is parametrised and validated.